Analisis Hukum Terhadap Konsep Riba Dalam Transaksi Jual BeliOnline Menggunakan Shopee Pay Later Pada Perspektif KompilasiHukum Ekonomi Syariah - Antony Charles; Wiwin Mochtar Wiyono; Ferryani Krisnawati; Eti Mul Erowati (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2024)
The purpose of this research is to determine the mechanism for using Shopee PayLater in the Shopee applicationand the views of the compilation of sharia economic law on the mechanism of buying and selling contracts usingShopee PayLater. This research uses an empirical normative juridical approach and the type of research uses aqualitative approach which includes the results of online surveys and interviews, with various written informationthat explains the buying and selling mechanism using Shopee PayLater payments in the view of the ShariaEconomic Law Compilation. This data relates to Shopee PayLater service provisions, payment systems, billing anduser statements. The techniques used by the author are direct and online interviews as well as literature study. Theresults of this research are that the requirements for activating Shopee PayLater are that you must have a Shopeeaccount that has been verified by Shopee and must have an ID card to activate it. The payment system is ininstallments 2 times, 3 times, 6 times and 12 times per month. Bill payments can be made via m-banking, ATM,Indomart, Alfamart, or other payments. The use of Shopee PayLater is included in the qardh contract which hasbeen regulated in the Compilation of Sharia Economic Law in article 20 paragraph 36 which explains the meaningof Qard and the articles related to qard in the use of Shopee PayLater, namely in article 606, article 607, article 608,Article 609 and Article 611. According to several legal opinions, Shopee PayLater can be said to be usury when thereis an ziyadah or additional element required in advance by the paylater publisher for its consumers. Included in thetype of debt usury which is prohibited. However, if Shopee PayLater charges additional fees then it is not usury. Aslong as the additional costs are counted as services or ijarah.Keywords: Usury, Online Buying and Selling, Shopee PayLater, Compilation of Sharia Economic Law